2017
DOI: 10.1186/s40575-017-0042-8
|View full text |Cite
|
Sign up to set email alerts
|

Osteosarcoma inheritance in two families of Scottish deerhounds

Abstract: BackgroundOsteosarcoma is the most common neoplastic disease in Scottish Deerhounds. For Deerhounds, a 2007 population-based study concluded that a single dominant genetic factor largely governed disease risk. For Greyhounds, Rottweilers, and Irish Wolfhounds, a 2013 genome-wide association study found multiple genetic markers in each breed, with each marker only weakly associated with the disease.We obtained from two breeders the pedigrees, age (if alive) or age at death, and osteosarcoma status for two famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…[33] A single autosomal genetic risk factor for OS has been identified in Scottish deerhounds. [32, 39] These studies, together with a study documenting that breed-based genetic backgrounds affect the tumor karyotypes in canine OS, suggest a strong contribution of the genetic background to the development of the OS phenotype in these breeds. [30] However, there is also argument that the prevalence of OS in large and giant breed dogs may be due to size instead of breed—a case in point being that even though greyhounds and whippets are in the same phylogenetic microsatellite cluster, disease prevalence is very different between the 2 breeds, with the greyhound much more commonly affected.…”
Section: Discussionmentioning
confidence: 99%
“…[33] A single autosomal genetic risk factor for OS has been identified in Scottish deerhounds. [32, 39] These studies, together with a study documenting that breed-based genetic backgrounds affect the tumor karyotypes in canine OS, suggest a strong contribution of the genetic background to the development of the OS phenotype in these breeds. [30] However, there is also argument that the prevalence of OS in large and giant breed dogs may be due to size instead of breed—a case in point being that even though greyhounds and whippets are in the same phylogenetic microsatellite cluster, disease prevalence is very different between the 2 breeds, with the greyhound much more commonly affected.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from canine Genome Wide Association Studies (GWAS) of osteosarcoma imply that both modes of inheritance may apply for osteosarcoma risk alleles, and such studies have so far identified risk-associated polymorphisms at the Insulin Growth Factor-1 (IGF-1) locus, which is associated with large body size, and at other loci, such as the Cyclin Dependent Kinase CDKN2A/B region [ 4 , 7 , 10 , 11 , 13 ]. However, only Irish Wolfhounds, Rottweilers and Greyhounds have been included in existing canine osteosarcoma GWAS, meaning that alternative causal variants in other breeds could have been missed while, to-date, protected breeds have been ignored altogether [ 10 , 13 , 16 ]. Overall, the breed-associated genetics of osteosarcoma need to be examined in more detail in order to facilitate the discovery of novel osteosarcoma risk-associated genetic variants [ 17 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…This means that large breed genetics are necessary but not sufficient to induce osteosarcoma. However, non-genetic risk factors for canine osteosarcoma are poorly understood, and the identification of breeds predisposed to, and protected from, osteosarcoma will generate hypotheses for research in this field [ 16 , 20 ]. In humans, osteosarcoma is rare, affecting 3 individuals per million in the United States each year.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was determined that a study with 1756 cases and 905,211 controls would give >99.99% power to detect differences in the odds of osteosarcoma between the Rottweiler (reported to be the most predisposed breed in previous studies) and crossbreeds ( [58] with methodology from [59] table 6.3). This calculation was based on a previously reported osteosarcoma prevalence of 0.03% amongst crossbreeds and 1.14% amongst Rottweilers, with Rottweilers comprising 1.17% of UK dogs [60,61].…”
Section: Methodsmentioning
confidence: 99%